Penatalaksanaan Fisioterapi Pada Post Orif Fracture 1/3 Distal Radius: A Case Report - Olga Nurkhalida Nashrah; Andika Yullian Marros (Journal of Health and Therapy, 2022)
This study aims to review the management of physiotherapy in cases of fracture 1/3 of the distal radius. A study witnesses that this case is an enormous incident of hand fracture, accounted 17-25% of the total. A 24-years-old woman (as a student) experienced a motorcycle accident on 29th of July 2021. After being observed, she was diagnosed 1/3 distal radius fracture, ulna dislocation, and mild cerebral oedema. The doctor conducting open reduction internal fixation (ORIF) surgery to the patient on 30th of July 2021. Moreover, there were pain, oedema, and limitation of wrist in her incise area felt by the patient after that surgery. The visited physiotherapy clinic 8 times (2 times a week) with 4 evaluations every week. The patient was provided some treatments such us infrared (IR), TENS, static contraction, ROM exercise, strengthening, and release. The results of the evaluation for 8 treatments showed that there were changes in aspects of pain, edema, MMT and ROM in the wrist & elbow region. The recovery process for fractures accompanied by fixation of the bone, both internal and external, can lead to potential problems that can occur in patients with postoperative fractures of the distal 1/3 of the radius. It is very important to start physiotherapy as early as possible to improve circulation, prevent postoperative problems or complications and speed up the patient's recovery.